Effect of natural rubber latex on the conducting state of polyaniline blends determined by Raman spectroscopy - Job, A. E.; Constantino, CJL; Mendes, TSG; Teruya, M. Y.; Alves, Neri [UNESP]; Mattoso, LHC (Wiley-Blackwell, 2003)
Blends possessing the elastomeric properties of natural rubber (NR) and the conducting properties of conducting polymer (polyaniline, PANI) were obtained, which are promising for further application in deformation sensors. Blends containing 20% (v/v) of PANI in 80% of NR latex were fabricated by casting in the form of free-standing films and treated either with HCl or with corona discharge, which lead PANI to its conducting state (doping process). Characterization was carried out by Raman spectroscopy, d.c. conductivity and thermogravimetric analysis. Evidence for chemical interaction between PANI and NR was observed, which allowed the conclusion that the NR latex itself is able partially to induce both the primary doping of PANI (by protonation) and the secondary doping of PANI (by changing the chain conformation). Further improvement in the primary doping could be obtained for the blends either by corona discharge or by exposing them to HCl the electrical conductivity reached in the blends was dependent on the doping conditions used, as observed by Raman scattering. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: natural rubber; polyaniline; doping; conductivity